The chinese pygmy dormouse Typhlomys cinereus chapensis Osgood, 1932 (Rodentia) in Vietnam - Tam, Nguyen Minh; Sung, Cao Van (Academia Journal of Biology, 2015)
The chinese pygmy dormouse Typhlomys cinereus chapensis Osgood, 1932 (Rodentia) in Vietnam